Inducible site-specific recombination in the brain - Kellendonk, Christoph; Tronche, François; Casanova-Hevia, Emilio; Opherk, Christian Henri; Schütz, Günther (Journal of molecular biology, 2002)
The Cre/loxP recombination system allows the generation of tissue-specific somatic mutations in mice. Additional temporal control of somatic mutagenesis is highly desirable, as this would permit a more precise analysis of gene function in complex systems such as the central nervous system. Extending our previous studies, we compared several ligand-regulated recombinases, in which the ligand-binding domain (LBD) of the progesterone receptor or the estrogen receptor was fused to the Cre recombinase. A fusion protein between the Cre recombinase and a truncated LBD of the progesterone receptor was chosen to obtain inducible recombination in the brain. This fusion protein can be activated by the synthetic steroid RU486, but not by the physiological hormone progesterone. Its expression was targeted to the brain using regulatory sequences of the calcium-calmodulin-dependent kinase IIα or the Thy-1 gene. Application of RU486 to the mice induced Cre-mediated recombination of a lacZ reporter transgene in the cortex and hippocampus, showing that spatially and temporally controlled gene targeting can be mediated in the brain.